Church in a Secularized Society - Mundadan C.M.I., M. (Journal of Dharma, 1980)
Roger Aubert et al., The Church in a Secularized Society, New York/Ramsey, N.J., Toronto: Paulist Press, London: Darton, Longman and Todd, 1978, pp, xxxii + 719 + 63, Unnumbered pages containing 90 illustrations, Price: £ 16·00.